PENGARUH KOMBINASI PELARUT EKSTRAKSI ETANOL 96%-ETIL ASETAT (1:1) DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) TERHADAP PERTUMBUHAN BAKTERI Bacillus subtilis - Hasani, Najwi; Muhammad Awaluddin Padjrin; Daipadli; Hayatus Sa’adah (Jurnal Insan Farmasi Indonesia, 2025)
The leaves of Pandan Wangi (Pandanus amaryllifolius Roxb.) are known for their antibacterial properties, containing bioactive compounds such as alkaloids, flavonoids, saponins, tannins, polyphenols, essential oils, steroids, and terpenoids. This study aimed to evaluate the antibacterial activity of ethanol-ethyl acetate (1:1) extract of Pandan Wangi leaves against Bacillus subtilis using the well diffusion method. The extract was prepared through maceration, and phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, phenols, and steroids. Antibacterial activity was assessed at concentrations of 1%, 5%, 10%, 20%, 30%, 40%, and 50%. The results indicated that the extract exhibited significant antibacterial activity at concentrations of 10% and above, producing inhibition zones of 8.39 mm, 10.33 mm, 11.27 mm, 13.37 mm, and 15.57 mm for 10%, 20%, 30%, 40%, and 50% respectively. No inhibition was observed at 1% and 5% concentrations. In conclusion, the ethanol-ethyl acetate extract (1:1) of Pandan Wangi leaves demonstrated effective antibacterial activity against B. subtilis at a minimum concentration of 10%, confirming its potential as a natural antibacterial agent.